EVA (ECONOMIC VALUE ADDED) DAN MVA (MARKET VALUE ADDED) SERTA PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Said Almaududi (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
This research aims to assess the company's performance on companies incorporated in the Indonesia Stock Exchange's LQ45 period 2005-2015 by using the concept of EVA and MVA and the concept of influence on stock prices. The results showed that in general the performance of companies that are incorporated in the LQ45 experienced EVA negative, it is possible the existence of the huge capital costs of each company. On the contrary, in general the performance of companies that are incorporated in the LQ45 experienced positive MVA, this illustrates that companies incorporated in LQ45 has managed to create a value added market for its shareholders. ANOVA test results obtained that EVA and MVA affect stock prices as the value of the company, it is likely because investors tend to use/exploit internal data companies in investment decision making.Keywords: EconomicValue Added (EVA) and Market Value Added (MVA)